ANALISIS PENGUKURAN KUALITAS PELAYANAN BANK SYARIAH DENGAN METODE FUZZY-SERVQUAL DIMENSI CARTER - Biki Zulfikri Rahmat; Anggita Ardianty; Trisna Wijaya (Ekonomi Islam, 2023)
This study aims to determine the quality of BJB Syariah services seen from the position of the gap that is formed between customer perceptions and perceptions. Improving service quality is one of the important points as an effort to develop Islamic banking in Indonesia. The method used in this research is a quantitative method with a descriptive-comparative approach. While the measurement method uses the fuzzy-servqual method with CARTER dimensions. The results of the study show that there are still many assessments with a gap between customer perceptions and perceptions that are negative. This shows that the quality of service expected by the client is not in accordance with the quality of service perceived by the client.